EFEKTIVITAS METODE EXPLORE ASK READ TELL HARVEST (EARTH) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN BAGI SISWA BERKESULITAN BELAJAR KELAS IV (CLASSROOM ACTION RESEARCH DI SDN 024/XI KEL. DUSUN BARU) - Ardini, Noli (Inspiratif Pendidikan, 2021)
This research is motivated by the problems found in class IV SDN 024 / XI Kel.Dusun Baru, Sungai Penuh City, Jambi Province. There are three students who have difficulty understanding the contents of a discourse reading text.Basically, students are already able to read, it's just that there are frequent additions, subtractions and omissions of letters when reading. During the learning process the teacher uses a demonstration method that explains the sub-theme of the three environments around me, then the teacher instructs the students to read the text entitled The Sun as a Source of Energy. After the reading activity is complete, there are three students who have problems understanding the contents of the discourse reading text.Therefore, researchers will use the explore ask read tell harvest (earth) method to improve reading comprehension skills for students having difficulty learning grade IV SD. The implementation of this research will be carried out in two cycles, each of which consists of: planning, implementing actions, observing and reflecting. Data collection techniques used were observation, documentation, and action tests. Based on the results obtained by the three fourth grade students on the ability to understand the contents of the discourse reading text, in the first cycle the results obtained were F 39%, Z 35% and R 52%. and in the second cycle the results obtained were F 65%, Z 66% and R 70%. Based on the data above, it can be concluded that students have improved in understanding the contents of a reading using the explore ask read tell harvest (earth) method.